A building's refurbishment knowledge-based decision support system. (21st November 2008) - Kaklauskas, Arturas; Zavadskas, Edmundas Kazimieras; Galiniene, Birute
The need to effectively integrate decision-making tasks, together with knowledge representation and visualisation tasks, inference procedures that model an expert's thinking process, has strained research attempts to integrate Decision Support Systems (DSS) with Knowledge Systems (KS) and multimedia in the direction of the development of knowledge-based DSS. The authors of this paper participated in the programme Framework 6 project BRITA in PuBs. One of the project's goals was to develop a Building Refurbishment Knowledge-based Decision Support System (BR-KDSS). In order to demonstrate the integration of knowledge and DSS, a BR-KDSS will be considered as an example.